Industrial operation feasibility for red gypsum-based brick manufacturing - Mohd Amirul Hakim, Sidek; R. M., Yunus; Ahmad Khan, Mohamad Al-Nizar Khan; Islam, Muhammad Remanul (Asian Online Journals, 2019)
The red gypsum (RG) waste is one of the major solid wastes generated in Malaysia. Currently the RG is mainly sent to secured landfill within the premise of the waste generators. In this study, the RG was investigated for its potential to be used as replacement for cement and sand in the manufacturing of cement brick using industrial brick manufacturing facility.An industrial guideline for RG brick manufacturing industry was established based on the outcome of this study. The guideline can be used by RG brick manufacturer to select the best water/cement (w/c) ratio to be used in the RG brick manufacturing for a specific market segment in order to maximize its profit and competitiveness.